GIS-material for the archaeological project: Nybble Golf Club - Haddorp - Swedish National Heritage Board, UV Öst (Uppsala University, 2014)
The information in the abstract is translated from the archaeological report:
Due to a planned expansion of the golf course at Nybble golf club in Haddorp, Vikingstad parish, Linköping municiplaity, the Swedish National Heritage Board's contract archaeology division, UV Öst, has performed a stage 2 survey and a preliminary investigation. During the preliminary investigation, while the protected area south of RAÄ 196, 215 and 218 was being delimited, remains of a settlement damaged by ploughing were discovered. During the survey, remains from another settlement were found in one of the areas. The field work was performed in June 2005.

Purpose:

The information in the purpose is translated from the archaeological report:
The purpose of the preliminary investigation was to determine the type, intensity and extent of the archaeological remains, and, if possible, to date them. The purpose of the survey was to investigate whether the affected area contained any archaeological remains.

The ZIP file consist of GIS files and an Access database with information about the excavations, findings and other metadata about the archaeological survey.

Informationen i sammanfattning är hämtad ur rapporten för undersökningen:
Riksantikvarieämbetet UV Öst har utfört en arkeologisk förundersökning och utredning etapp 2 vid Nybble Golfklubb, Haddorp, Vikingstad socken, Linköpings kommun. Anledningen var en planerad utbyggnad av golfbanan. Vid förundersökningen avgränsades fornlämningsområdet söder om fornlämningarna RAÄ 196, 215 och 218 då rester av en sönderplöjd boplats hittades. Vid utredningen hittades lämningar från en förhistorisk boplats i ett av områdena. Arbetet utfördes i juni 2005.

Syfte:

Informationen i syfte är hämtad ur rapporten för undersökningen:
Vid förundersökningen var syftet att klargöra art och intensitet av lämningarna sant att begränsa fornlämningens utbredning och om möjligt datera lämningarna. Vid utredningen var syftet att konstatera om det finns fast fornlämning inom de utpekade områdena.

ZIP-filen innehåller GIS-filer samt en Access datafil vilka innehåller information om schakt, fyndföremål, lämningstyper samt annan metadata om den arkeologiska undersökningen.
GIS-material för arkeologiskt projekt: Nybble Golfklubb - Haddorp
Keywords: Bronze Age; bronsålder; Iron Age; järnålder; HISTORY; HISTORIA; History and Archaeology; Historia och arkeologi; Archaeology; Arkeologi